Upregulation of SPINK2 in acute myeloid leukemia - Gezer Sümbül; Emrence Zeliha; Elverdi Tuğrul; Ar Muhlis Cem; Salman Yaylaz Burcu; Paçal Ferda; Ünüvar Ayşegül; Sarıman Melda; Eşkazan Ahmet Emre; Karaman Serap; Salihoğlu Ayşe; Karakaş Zeynep; et al. (Advances in Laboratory Medicine, 2023)
Acute myeloid leukemia (AML) is a highly heterogeneous disease. Although patients can be classified into risk groups based on their genetic changes, the prognosis of disease within these categories varies widely. This situation raises the need to search for new molecular markers related to AML. Serine peptidase inhibitor Kazal type 2 (SPINK2) has recently been reported to be upregulated in AML and associated with poor outcomes by meta-analysis and in a limited number of AML patients.